PERAN KURIKULUM MERDEKA DALAM PENGEMBANGAN KOMPETENSI ABAD 21 DI SEKOLAH MENENGAH - Enny Zarvianti; Bachtiar Sjaiful Bachri; Lamijan Hadi Susarno (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The Independent Curriculum implemented in Indonesia aims to prepare students to face the global challenges of the 21st century, by placing emphasis on the development of critical, creative, collaborative, and effective communication skills. The curriculum is designed to equip students with relevant competencies in an ever-changing world, while developing the positive character and attitudes needed in society. This article aims to examine the role of the Independent Curriculum in the development of 21st century competencies at the high school level through a literature review approach. Based on a review of various relevant literature, it was found that the Independent Curriculum provides opportunities for students to develop core competencies in the 21st century, such as critical thinking, creativity, collaboration, and having effective communication skills. This can be achieved through the application of a project-based learning approach that encourages students to learn through direct experience, authentic assessments that better describe the achievement of student competencies in real contexts, and strengthening the Pancasila student profile which is the foundation of student character. The Pancasila student profile itself prioritizes attitudes such as diversity, independence, and social responsibility, which are very relevant to the needs of the increasingly complex world of work and global society. The results of this study show that the implementation of the Independent Curriculum can strengthen students' skills that are indispensable to face the challenges of the dynamic world of work and prepare them to become active and adaptive citizens in a global society. Thus, the Independent Curriculum has an important role in shaping the young generation who not only have knowledge, but also skills and attitudes that are in accordance with the demands of the times.